ASSESSMENT OF THE EMOTIONAL SPHERE OF SCHOOLCHILDREN WITH DISADAPTION - Saliev , Abduboriy; Arzikulov, Abdurayim (Medical science of Uzbekistan, 2023)
The purpose of our work was to study the characteristics of psycho-emotional reactions in schoolchildren with maladaptive disorders. The material and method for the study were schoolchildren with maladaptive disorders aged 7-11 (30 boys and 32 girls) and 12-17 (26 boys and 24 girls) years old. The studies were carried out using the frustration tolerance technique of S. Rosenzweig. Results and discussions: Analysis of our results shows the presence of psycho-emotional parallels in all children with manifestations of maladjustment. The degree of response and the quality of changes in the psycho-emotional profile depend on the age of the subjects. Conclusions. In children and adolescents - schoolchildren with maladaptation reactions, characteristic types and direction of emotional response to frustration are revealed; extrapunitive (externally blaming) and less often impunitive (evasive) orientation is manifested more often.